Is There Benefit to Free Over Pedicled Vascularized Grafts in Augmenting Tibial Intercalary Allograft Constructs - Manfrini, M.; Bindiganavile, S.; Say, F.; Colangeli, M.; Campanacci, L.; Depaolis, M.; Ceruso, M. (Springer New York LLC agents@lww.com, 2017)
Background: Intercalary reconstruction of tibial sarcomas with vascularized fibula autografts and massive bone allografts is reliable with predictable long-term results. However, inadequate data exist comparing free and pedicled vascularized fibula autografts in combination with a massive bone allograft in patients undergoing intercalary tibia reconstructions. Questions/Purposes: Among patients undergoing large-segment intercalary allografting, we sought to compare supplemental free vascularized fibular autografts with supplemental pedicled vascularized fibular autografts, in terms of (1) oncologic results, (2) complications associated with surgery, (3) Musculoskeletal Tumor Society (MSTS) scores, and (4) surgical time. Methods: Between 1994 and 2013, we treated 320 patients, younger than 40 years, with tibial sarcomas. Thirty-five patients (11%) underwent amputations. One hundred ninety-five patients (61%) were treated with intraarticular resection of the tibia, which constituted 104 tumor endoprostheses, 63 proximal tibia allograft prosthetic composites, 21 osteoarticular allografts, and seven arthrodeses with allografts. Ninety patients (28%) underwent joint-sparing intercalary reconstruction. Forty-one (13%) of these 90 patients were treated with allografts alone, two (1%) with vascularized fibula grafts, and 47 (15%) with intercalary allografts supplemented by autografts (free fibular autografts, 22 patients, 7%; pedicled fibular autografts, 25 patients, 8%). During the study period, we used free vascularized fibular autografts in association with massive bone allograft for a resection longer than 12 cm with a very small periarticular residual segment. The choice for using a pedicled fibula harvested in the ipsilateral leg initially was for patients having only diaphyseal resections and the indication was later extended to intraepiphyseal osteotomies with a small periarticular residual segment. The goals of this study are to present the long-term results in this group of patients and compare their results based on the type of vascularized fibula harvest. There were 33 male and 14 female patients with mean age of 14 ± 6 years. The median followup was 84 months (range, 7–231 months). No patients were lost to followup before 1 year. Four patients died and were not available for followup after 18 months. The mean tibia resection length was 15 ± 4 cm and mean length of the harvested vascularized fibula was 18 ± 4 cm. Results: Overall 5- and 10-year oncologic survival rates in this study were 87% ± 5% and 83% ± 6% respectively. With the numbers available, we observed no difference in survivorship free from death from disease between the study groups (85% ± 8% [95% CI, 174–232 months] of the free vascularized group versus 82% ± 8% [95% CI, 148–206 months] of the pedicled fibula graft group; p = 0.741). At last followup, 40 patients had no evidence of disease and seven had died of disease. Local recurrence was observed in two patients in the supplemental free vascularized fibula group and three patients in the supplemental pedicled vascularized fibula group, whereas metastases was observed in eight patients. With the numbers available, we observed no difference in the proportion of patients experiencing surgical complications between those treated with free vascularized fibula grafts and those treated with pedicled grafts (eight of 22 [36%] versus nine of 25 [36%] respectively; p = 0.605). With the numbers available, we observed no difference in mean MSTS scores between patients treated with free vascularized fibula grafts and those treated with pedicled grafts (24 ± 9 versus 25 ± 8; mean difference, 0.48; 95% CI, 0.54–4.6; p = 0.858). Mean surgical time was longer in the free vascularized fibula and massive bone allograft group at 9.4 ± 1.7 hours compared with that of the pedicled vascularized fibula and massive bone allograft group at 5.7 ± 1.3 hours (mean difference, 3.73 hours; 95% CI, 2.8–4.6 hours; p ≤ 0.001). Conclusions: Intercalary reconstruction of tibia sarcomas with massive bone allografts supplemented with vascularized fibula grafts provide predictable results. Complications occur as expected in a biologic reconstruction, but are salvageable, preserving the original construct. The pedicled fibula can be an alternative to a free contralateral fibula for intraepiphyseal resections. Comparative technical ease, shorter surgical time, avoidance of additional microvascular anastomosis, and avoidance of surgery on the contralateral leg are notable advantages of pedicled vascularized fibula over free fibula grafts to supplement allografts when indicated in intercalary tibia resections. Level of Evidence: Level III, therapeutic study. © 2016, The Association of Bone and Joint Surgeons®.